Is PM1 similar to PM2.5? A new insight into the association of PM1 and PM2.5 with children's lung function. (December 2020) - Yang, Mo; Guo, Yu-Ming; Bloom, Michael S.; Dharmagee, Shyamali C.; Morawska, Lidia; Heinrich, Joachim; Jalaludin, Bin; Markevychd, Iana; Knibbsf, Luke D; Lin, Shao; Hung Lan, Steve; Jalava, Pasi; et al.
Highlights: Long-term PM1 and PM2.5 exposure can lead to decreased lung function in children. Association of PM1 with children's lung function are larger than PM2.5 . PM1 and PM2.5 are associated with children's large/small airways in early/late life. Abstract: Experimental data suggests that PM1 is more toxic than PM2.5 although the epidemiologic evidence suggests that the health associations are similar. However, few objective exposure data are available to compare the associations of PM1 and PM2.5 with children lung function. Our objectives are a) to evaluate associations between long-term exposure to PM1, PM2.5 and children's lung function, and b) to compare the associations between PM1 and PM2.5 . From 2012 to 2013, we enrolled 6, 740 children (7–14 years), randomly recruited from primary and middle schools located in seven cities in northeast China. We measured lung function including forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), peak expiratory flow (PEF), and maximal mid-expiratory flow (MMEF) utilizing two portable electronic spirometers. We dichotomized continuous lung function measures according the expected values for gender and age. The spatial resolution at which PM1 and PM2.5 estimated were estimated using a machine learning method and the temporal average concentrations were averaged from 2009 to 2012. A multilevel regression model was used to estimate the associations of PM1, PM2.5 exposure and lung function measures, adjusted for confounding factors. Associations with lower lung function were consistently larger for PM1 than for PM2.5 . Adjusted odds ratios (OR) per interquartile range greater PM1 ranged from 1.53 for MMEF (95% confidence interval [CI]: 1.20–1.96) to 2.14 for FEV1 (95% CI: 1.66–2.76) and ORs for PM2.5 ranged from 1.36 for MMEF (95%CI: 1.12–1.66) to 1.82 for FEV1 (95%CI: 1.49–2.22), respectively. PM1 and PM2.5 had significant associations with FVC and FEV1 in primary school children, and on PEF and MMEF in middle school children. Long-term PM1 and PM2.5 exposure can lead to decreased lung function in children, and the associations of PM1 are stronger than PM2.5 . Therefore, PM1 may be more hazardous to children's respiratory health than PM2.5 exposure.